전형적 비전형적 성역할 VTR 프로그램이 유아의 성역할 고정관념에 미치는 효과 - 홍연애(Yeon Ae Hong); 정옥분(Ock Boon Chung) (Korean Journal of child studies, 1993)
The primary purpose of this study was to develop an educational tool that can be used in teaching young children about different types of sex roles. The secondary purpose was to observe and analyze the effects of watching different sex role video programs on preschool children's sex role stereotypes and to determine the lasting effects. The subjects of this study were 89 six year-old kindergarten children, forty five were girls and forty-four boys. Each child was interviewed individually and tested at three different points in time: 1 week before the treatment, immediately after the treatment, and 4 weeks after the treatment. Three different statistical procedures were used in analyzing the data: ANOVAs for sex differences in sex role stereotypes. ANCOVAs for the different effects of traditional sex role programs and reversed sex-typed sex role programs, and ANCOVAs and Lindquist type III ANOVAs for the lasting effects of the treatment. The findings of the study indicated that (1) the children showed sex differences in the scores of sex role stereotypes of own, opposite sex and child activity; (2) there were differences in the scores of sex role stereotypes in terms of own and opposite sex. That is, viewing the reversed sex-typed programs caused a decrease in children's sex role stereotypes; and (3) the traditional and reversed sex-typed sex role programs tested four weeks after treatment showed significant lasting effects of sex role stereotypes in terms of opposite, composite and adult activity. In conclusion, the results of this study suggest that the sex stereotypes of kindergarten children can be changed through sex role VTR programs.